Federal Theatre, 1935-1939 : Plays, Relief, and Politics - De Hart, Jane Sherron (Book collections on Project MUSE., 1967)
The WPA Theatre Project-conceived as a relief measure, a work program, and an artistic experiment-enjoyed a brief but lively existence. With skill and sensitivity Mrs. Mathews explores its turbulent history from its ambiguous origins in 1935 to its tragic demise in 1939. The book recreate: the atmosphere of the era, and conveys a vivid sense of the Joys, frustrations, and personal sacrifices undergone by those dedicated few who recognized the need for an American People's Theatre. Mrs. Mathews also provides a detailed account of the Congressional hearings which occasioned the disbanding of t.